2020
DOI: 10.3390/biom10111560
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Ykt6 SNARE Domain Regulates Its Membrane Recruitment and Activity

Abstract: Sensitive factor attachment protein receptors (SNARE) proteins are important mediators of protein trafficking that regulate the membrane fusion of specific vesicle populations and their target organelles. The SNARE protein Ykt6 lacks a transmembrane domain and attaches to different organelle membranes. Mechanistically, Ykt6 activity is thought to be regulated by a conformational change from a closed cytosolic form to an open membrane-bound form, yet the mechanism that regulates this transition is unknown. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…S8 B , step two). Supporting our findings, a phosphorylation driven membrane recruitment for Ykt6 was also reported while this paper was under review ( 43 ). The conformational mechanism of activation might not be restricted to Ykt6 since the S174 phosphorylation site is also evolutionarily conserved across other R-SNARE proteins ( 44 ).…”
Section: Discussionsupporting
confidence: 89%
“…S8 B , step two). Supporting our findings, a phosphorylation driven membrane recruitment for Ykt6 was also reported while this paper was under review ( 43 ). The conformational mechanism of activation might not be restricted to Ykt6 since the S174 phosphorylation site is also evolutionarily conserved across other R-SNARE proteins ( 44 ).…”
Section: Discussionsupporting
confidence: 89%
“…In other words, phosphorylation of Ser174/Ser177 regulates both conformational state of Ykt6 and its protein binding property in mammals and C. elegans , but phosphorylation only affects the protein binding capacity of Ykt6 in yeast. Besides Ser174, several other phosphorylation sites on Ykt6 have been identified ( 15 , 16 ), we anticipate that more regulatory mechanisms and delicate differences across species are yet to be discovered.…”
Section: Discussionmentioning
confidence: 99%
“…The conformational state of the longin SNARE Ykt6 is tightly related to its cellular localization and function. It has been revealed that the conformational state could be regulated by the lipid modification ( 11 , 22 ) and phosphorylation ( 15 , 16 , 17 ). However, it is intriguing that the function and conformational regulation of Ykt6 exhibit differences among various species ( 17 , 18 , 19 , 20 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation